Human Homosexual Preferences from the Perspective of Evolutionary Psychology - Yangli TIAN; Ying JI; Ailan WAN (Yixue yu zhexue, 2025)
In the process of human evolution, reproduction has taken many diverse forms. The exploration of homosexual behavior aims to reveal the mystery of its persistence from the perspective of evolutionary psychology. By integrating current theories and empirical research in evolutionary psychology regarding homosexual behavior, this analysis examines the phenomenon of homosexuality in human society from three dimensions: genetic inheritance, hormonal regulation, and social influence. It points out that these three factors intertwine and jointly affect individual homosexual behavior, indirectly promoting human reproduction, and further clarifies the significance of the existence of homosexuality. In the historical context of social change, this helps enhance the understanding of homosexual behavior, promotes the evolutionary value of social development, and provides new ideas for future researchers to explore the intrinsic mechanisms of homosexual evolution and interdisciplinary studies, encouraging multi faceted reflections on the issue of "survival of the fittest".